2023
DOI: 10.4187/respcare.10507
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Arterial CO2Retention in Patients With Moderate or Severe ARDS

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The potential mechanisms behind this could be attributed to the fact that the blockage or overdistention of alveoli in patients with hypercapnia could cause the instability of pulmonary units and an imbalance in the ventilation/blood flow ratio [74]. Further studies confirmed that hypercapnia was associated with mortality and that extracorporeal CO 2 removal treatment could correct hypercapnic acidosis, reduce ventilation days and facilitate pulmonary-protective ventilation [42,[75][76][77]. Therefore, strategies aimed at lowering the OSI value could potentially provide greater benefits to patients with hypercapnia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential mechanisms behind this could be attributed to the fact that the blockage or overdistention of alveoli in patients with hypercapnia could cause the instability of pulmonary units and an imbalance in the ventilation/blood flow ratio [74]. Further studies confirmed that hypercapnia was associated with mortality and that extracorporeal CO 2 removal treatment could correct hypercapnic acidosis, reduce ventilation days and facilitate pulmonary-protective ventilation [42,[75][76][77]. Therefore, strategies aimed at lowering the OSI value could potentially provide greater benefits to patients with hypercapnia.…”
Section: Discussionmentioning
confidence: 99%
“…net) [36][37][38]. We identified 21 covariates for further analysis based on literature review, our priori knowledge and the minimally sufficient adjustment set, including demographics [39,40] (age, gender and ethnicity), BMI [41], PaCO 2 [42], hemoglobin [43], comorbidities (ARDS, COPD, CKD, AKI, malignancy, HF and diabetes) [44][45][46][47][48], ventilation parameters (PEEP, plateau pressure, tidal volume, OSI at baseline) [49], APS-III score and treatment (dialysis, NMBAs and vasopressor therapy) [50][51][52].…”
Section: Directed Acyclic Graphsmentioning
confidence: 99%
“…(Gorman et al, 2022). Besides, stage 6 also presents CO 2 retention lowering the pH level of the patient and adding more deleterious outcomes for ARDS (Peschel et al, 2021;Maamar et al, 2023).…”
Section: Acute Respiratory Distress Syndrome (Ards): An Overviewmentioning
confidence: 99%
“…The combination of cellular debris in the fluid and atelectasis renders it impossible for the oxygen to get into the capillary membrane in stage 5. In contrast, stage 6 shows pulmonary tissue fibrosis, which indefinitely restricts the gas exchange between the alveoli and the membrane, as well as carbon dioxide retention in the blood (Ohshimo, 2021;Peschel et al, 2021;Gorman et al, 2022;Maamar et al, 2023).…”
Section: Main Factors Promoting the Development Of Ardsmentioning
confidence: 99%